How emotions from content social relevance mediate social media engagement: evidence from European supermarkets during the COVID-19 pandemic - Ballerini, Jacopo; Alam, Gazi Mahabubul; Zvarikova, Katarina; Santoro, Gabriele (Emerald Publishing Limited, 2023)
Purpose: The purpose of this study is to examine the antecedents of consumer engagement with supermarkets' social media accounts. Drawing on regulatory fit theory and social sharing of emotions theory, the authors test if the content posted on the social media brand pages of supermarkets dealing with a topic of high social relevance, such as the COVID-19 pandemic, stimulates social media consumer engagement and if and how the engagement is mediated by the arousal of positive and negative emotions. Design/methodology/approach: The authors retrieved data from the Facebook accounts of the top 20 European supermarkets identified in the Deloitte 2020 Global Powers of Retailing report during the first wave of the pandemic from 1 March to 30 June 2020, collecting a sample of 2,524 posts from 8 different countries. After a content analysis to classify COVID-19 content, the authors applied the Baron and Kenny (1986) methodology to verify the hypothesised relationships. Findings: The findings highlight a positive direct relationship between the social relevance of a topic (COVID-19) and social media consumer engagement mediated by the arousal of positive and negative emotions. Originality/value: To the best of the authors’ knowledge, this is one of the earliest empirical research using Facebook data to investigate the role of the social relevance of content as an antecedent of social media consumer engagement with a specific focus on supermarkets. The paper contributes to the stream of social media literature investigating the antecedents of social media engagement behaviour, exploring the role of topics' choice and aroused emotions, which to date are both under-investigated.